Invariance Analysis and Conservation Laws of a Modified (2+1)-Dimensional Ablowitz-Kaup-Newell-Segur Water Wave Dynamical Equation - Seele, M.F.; Muatjetjeja, B.; Motsumi, T.G.; Adem, A.R. (Journal of Applied Nonlinear Dynamics, 2026)
In this paper, we investigate a modified (2+1)-dimensional Ablowitz-Kaup-Newell-Segur (mAKNS) water wave equation. The method of symmetry analysis will be employed to find exact solutions of the mAKNS equation. In addition, we will implement the method of the multiplier approach to search for the admitted conserved vectors of this equation. Furthermore, a physical interpretation showing solution wave structures, density plots and wave propagation will be presented. The results obtained can be used to investigate further interaction of water waves in a variety of localized structures and high-dimensional models in other areas of nonlinear science.